Estudo de resistência mecânica do concreto compactado com rolo com emprego de material fresado asfáltico para base de pavimentos - Borré, Gracieli (2017)
The increase in traffic volume and the appearance of heavier vehicles are causing a greater degradation and deformation in the Brazilian road network, consequently raising maintenance costs, forcing managers and researchers to find new alternatives to improve utilization of materials, decreace energy consumption used in the executions, streamline restoration interventions, and more. Another important factor that stands out is the environmental issue, where it is directly affected in the construction and maintenance of highways, whether in the consumption of natural materials, in the movements of lands, in the fuels used, etc. The Rolled Compacted Concrete (RCC) appears as a material that fits within this perspective, since, in some cases, it has as a proposal to reduce the cement consumption and the time of execution, And it still has a long service life without a need for maintenance, thus being technically and economically attractive. Another point in your favor is the fact that the same equipment as the asphalt paving is used. Still the RCC, after being hardened, for a given cement consumption may have similar or superior characteristics to the conventional vibrated concretes. One of the characteristics of concrete in general is that it allows the incorporation of other materials, such as reclaimed asphalt pavement (RAP). This has a positive impact on the concrete construction economy. The objective of this work was to analyze three mechanical strength of roller compacted concrete (RCC), with partial replacement of the large aggregate by RAP, in the percentages of 10% and 30% for use in pavement bases, with different cement consumption in different curing ages. The tested mixtures were dosed with 100 and 150 kg of cement per cubic meter, typical values for RCC used in bases layers, totaling in six researched mixtures. The properties studied were simple compression strength, tensile strength by diametrical compression and the tensile strength in the flexion at 7 and 28 days of cure. The effects of RAP percentage, cement consumption and curing time were analyzed by compacting the test specimens in the intermediate energy. The main results showed that the performance the samples of RCC with 10% of RAP is superior to conventional ones. However, there is a decreaming resistance when the amount of RAP increases to 30%. The RCS of the samples varied from 5,74 to 11,42 MPa at 7 days and from 6,17 to 16,27 MPa at 28 days of cure. The RTCD ranged from 0,56 to 1,73 MPa in the 7 days and 0,77 to 2,27 MPa in the 28 days. The RTF obtained values ranging from 0,55 to 1,6 MPa at 7 days cure and 0,87 to 1,96 MPa at 28 days cure. The great influence of curing time on resistances is remarkable.. As for cement consumption, it is possible to affirm that there is a significant improvement in the resistance when a higher consumption of cement is used.